EX-VOTOS MIDIÁTICOS E A RECONSTRUÇÃO DA IDENTIDADE DA REVISTA AVE MARIA A supressão dos ex-votos no início da década de 1970 - Gordo, Luís Erlin Gomes (2014)
In popular Catholicism, the devout finds his own ways to manifest his faith, which at times are very far from the orthodoxy of the Church. The exvotos are clear examples of the appropriation of some elements of the Catholic tradition and their application in the faithfuls daily life. In 1898, when the Ave Maria magazine was first published , readers were encouraged to attest Gods granted favours through some saints. Thus the category granted graces was issued in the magazine; those were letters from the faithful giving evidence of granted miracles. After the Vatican Council II , by the end of the 1960s , the Catholic Church tried to purify faith , mainly in Latin America. The devotional Activities such as faith in saints, promises and exvotos were clearly contested. At that time the Ave Maria magazine suppressed the written release of exvotos to the media. The aim of this research is to understand the communicative process related to the fact mentioned above. The methodology was based on bibliographical and documentary research.